Islamic Banking and Global Financial Crises: A Review of Liquidity Risk Management - AbdulFattah AbdulGaniyy; Ibraheem Alani AbdulKareem (Economia: Journal of Economics and Management, 2022)
The objective of this conceptual paper is to describe the resilience of Islamic banks during the 2008 and 2009 global financial meltdown. The growth of complex financial instruments which was aimed at spreading risk actually increased instability due to market fluctuations and speculative activities resulted to the Global Financial Crisis (GFC). Inadequate liquidity is the immediate cause of financial meltdown. The paper reviews the causes of liquidity risk in Islamic banks which is based on Shariah (Islamic Law) that prohibits charging of interest in business transactions. The study highlights the challenges of Islamic banks on liquidity in spite of its resilience during the crisis. Major causes of liquidity risk in Islamic banks were also discussed. The paper concludes with managerial and policy implications and the need to address the problem of managing liquidity risk in Islamic banks against possible future financial crisis.